Intention to practice reduce, reuse & recycle (3R) among expatriates working in Malaysia - Mohd Ali, Muhamed Salim; Raja Yusof, Raja Nerina (Human Resource Management Academic Research Society, 2018)
Malaysia continues to attract expatriates due to its economic conduciveness, hence the increasing number of expatriates do play a role in the recycling targets set by the Government to be achieved by year 2020. Therefore, it is important to understand expatriates behaviour with regards to green practices such as the intention to practice 3R. This study was conducted on 187 expatriates from 25 nationalities, concentrated in the Klang Valley. The results showed that green attitude and green practice consequences had positive relationships with the intention to practice 3R among expatriates working in Malaysia. Subjective norms and perceived control behaviour, on the other hand, was found to be insignificant. Results of this study provided further understanding of expatriates’ intention to practice 3R and what influence them to do so. Subsequent policy and theoretical implications are discussed in the paper.